The Social and Economic Impacts of Big Data on National Privacy and Identity - Rashid, Irfan Rashid (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2027)
The paper examines how financial transparency influences the extent of trust of philanthropists with Non-Governmental Organizations (NGOs) in Punjab, Pakistan. NGOs are also involved in solving social problems including poverty reduction, health, and education and their activities depend greatly on the donations of philanthropists. But there have been allegations of mismanagement of finances and poor transparency that have raised doubts among donors. Quantitative method was also used to collect data on 100 philanthropists using structured questionnaires to evaluate their financial transparency perceptions in NGO funds utilization. The findings indicate that there is a strong positive correlation between financial transparency and donor trust because philanthropists are keen on availability of financial reports, independent audits, and disclosure of funds. This paper indicates that NGOs need to emphasize on transparent financial dealings to develop trust among the donors who are willing to offer long-term assistance. The results indicate that the increased transparency of financial reporting can play an important role in improving the trust of philanthropists, which will eventually make NGOs sustainable and credible.